Development of Student Worksheets Based on Contextual Teaching and Learning Integrated Malang Culture for Elementary School Students - Ria Norfika Yuliandari; Maryam Faizah; Husni Mubarok; Dian Mustika Anggraini; Salsabila Salsabila (AL-ISHLAH: Jurnal Pendidikan, 2025)
This study aimed to develop a student worksheet based on Contextual Teaching and Learning (CTL), integrated with Malang culture, to improve fifth-grade students’ understanding of fractional operations. Incorporating local cultural elements into mathematics instruction is intended to increase student engagement and contextual comprehension. The research employed a Research and Development (RD) design using the ADDIE model, which includes five phases: Analysis, Design, Development, Implementation, and Evaluation. The worksheet was designed around seven CTL components: constructivism, inquiry, questioning, learning community, modeling, reflection, and authentic assessment. Data collection instruments included interviews, expert validation sheets, and student response questionnaires. Descriptive analysis was used to evaluate the validity and practicality of the product. Validation was conducted by four experts in material (84.70%), media (80%), language (93.33%), and teaching practice (97.5%), indicating that the worksheet was “very valid” and suitable for classroom use. Implementation with fifth-grade students showed enhanced engagement and understanding, particularly in solving addition and subtraction of fractions with unlike denominators. The integration of CTL strategies and local cultural content, supported by colorful visuals and contextual examples, created a more interactive and meaningful learning experience. Student feedback and performance gains demonstrated the worksheet's effectiveness in supporting conceptual understanding and increasing motivation. The developed CTL-based worksheet, enriched with Malang cultural context, is valid, feasible, and effective for improving fractional learning in elementary mathematics classrooms.